“We Can’t Let Go”: Navigating Dance in a (Post-)Conflict Society - Babina Devi; Debanjali Biswas (Conversations Across the Field of Dance Studies)
Violence and precarity in Manipur is its past and current. What becomes of dance when violence spills over to various parts of society? What does it mean to be haunted by unspeakable memories of violence and yet dance for self and community, region and nation? The essay is written collaboratively and individually by co-authors-practitioners and researchers who have worked on exhuming the sublimated tensions and contradictions in dance cultures of Manipur (India) in the last decade. Though chronologically years apart, they find ideological connections in the demands of the peoples from their government. On the back of historical and cultural circumstances, such demands, fear, or violence arise from exclusionary processes of being minority communities within the nation. Biswas conducted her doctoral fieldwork through agitation, riots and blockades during the Inner Line Permit (ILP) movement (2014-2016). Babina’s doctoral fieldwork began during months of COVID-19 pandemic (2020) and concluded in May 2023 as violent clashes between two ethnic communities broke out. “What will remain of our dances when we are gone?” is often asked of us during conversations with peoples; “we can’t let go” of hope or fear, they assert. The purpose of the essay is two-fold: we look back on methods, ethics and care involved in fieldwork with interlocutors who have witnessed violence, while we witnessed violent events ourselves. Secondly, we deliberate on observance of rituals and staged performances while our interlocutors grapple with experiences of loss, grief and trauma framed by conflict, exclusion, and an overall fraught silence to their demands. We further deliberate on what remains of dance in Manipur at a time of rising tensions and divisions.